Organizational Culture, Internal Auditors, and Fraud Prevention with Internal Control and Good Corporate Governance as Intervening - Efendi, Husnul Irfan; Sayekti, Yosefa; Irmadariyani, Ririn (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2024)
A survey conducted out by the Association of Certified Fraud Examiners (ACFE) Indonesia Chapter (2019) shows that the highest fraud cases in Indonesia are corruption. This type of research is explanatory research. The population in this study were all employees in the BLUD Puskesmas environment in Sumenep Regency. The sample selection used the Purposive Sampling method, totaling 210 respondents. The research results show that Organizational Culture has no effect on Fraud Prevention. The role of Internal Auditors influences Fraud Prevention. Organizational culture influences the effectiveness of internal control. The role of Internal Auditors influences the Effectiveness of Internal Control. Organizational culture influences the implementation of Good Corporate Governance. The role of Internal Auditors influences the Implementation of Good Corporate Governance. The effectiveness of Internal Control influences Fraud Prevention. Implementation of Good Corporate Governance influences Fraud Prevention. Organizational culture influences fraud prevention through the effectiveness of internal control. The role of Internal Auditors influences Fraud Prevention through the Effectiveness of Internal Control. Organizational culture influences fraud prevention through the implementation of good corporate governance. The role of Internal Auditors influences Fraud Prevention through the Implementation of Good Corporate Governance.